1954. A Randomized Study to Evaluate the Shedding and Immunogenicity of H1N1 Strains in Trivalent and Quadrivalent Formulations of FluMist in Children 24 to <48 Months of Age. (26th November 2018) - Mallory, Raburn; Nyborg, Andrew C; Kalyani, Rubana; Tsai, Lan-Feng; Block, Stan L; Dubovsky, Filip
Abstract: Background: The quadrivalent live attenuated influenza vaccine (LAIV4) showed reduced effectiveness for the A/H1N1 component of the vaccine in 2013–2014 and 2015–2016. To address this, new assays were used to identify H1N1 LAIV strains with improved replicative fitness and immunogenicity. In this study, we compared the shedding and immunogenicity of a new A/H1N1 strain (A/Slovenia), selected using the new assays, to a previous strain (A/Bolivia) with reduced effectiveness. Methods: Two hundred children aged 24 to <48 months were randomized 1:1:1 to receive two doses of a quadrivalent formulation of 2015–16 LAIV or a trivalent formulation of 2015–2016 LAIV, both containing the H1N1 A/Bolivia strain, or a quadrivalent formulation of the 2017–2018 LAIV containing the new H1N1 A/Slovenia strain (NCT03143101). Nasal and serum immune responses were assessed before Doses 1 and 2, and 28 days after Dose 2. Nasal shedding was assessed on Days 2, 3, 4, 5, and 7 after Dose 1, and Days 2, 4, and 6 after Dose 2. Solicited symptoms, adverse events, and serious adverse events were collected. Statistical testing was limited to the prespecified primary endpoint of hemagglutination inhibition (HAI) antibody responses. Results: A higher proportion of children shed the A/Slovenia vaccine strain than the A/Bolivia strain on Days 4–7 after Dose 1. The study met its primary endpoint, with significantly higher HAI antibody responses for the A/Slovenia strain after both the first and second doses of vaccine (Figure 1). Neutralizing antibodies and nasal immunoglobulin A (IgA) antibody responses were higher for the A/Slovenia than the A/Bolivia strain for both the trivalent and quadrivalent vaccine formulations. HAI antibody seroconversion rates (≥4-fold increase from baseline) for the A/Slovenia strain were similar to those seen in previous studies in which the H1N1 vaccine strain was highly efficacious (Figure 2). There were no significant safety findings. Conclusion: The new H1N1 A/Slovenia strain demonstrated improved immunogenicity compared with a previous strain with reduced effectiveness, and immune responses comparable to a highly efficacious H1N1 LAIV strain. These results support the use of LAIV4 as an important vaccine option. Disclosures: R. Mallory, MedImmune: Employee, Salary. A.C. Nyborg, MedImmune: Employee, Salary. R. Kalyani, MedImmune: Employee, Salary. L.F. Tsai, MedImmune: Employee, Salary. S.L. Block, AstraZeneca: Investigator, Research grant. F. Dubovsky, MedImmune: Employee, Salary.